2005
DOI: 10.1385/abab:125:2:127
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Glutathione Reductase From Chicken Liver and Investigation of Kinetic Properties

Abstract: Glutathione reductase was purified from chicken liver and some characteristics of the enzyme were investigated. The purification procedure was composed of four steps: preparation of homogenate, ammonium sulfate precipitation, 2',5'-ADP Sepharose 4B affinity chromatography, and Sephadex G-200 gel filtration chromatography. Owing to the four consecutive procedures, the enzyme was purified 1714-fold, with a yield of 38%. Specific activity at the final step was 120 enzyme unit (EU)/mg of protein. The purified enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…This activity value is very close to others reported for GRases purified from different sources Mannervik 1975, 1985;Chung and Hurlbert 1975;Dringen and Gutterer 2002;Serrano et al 1984). The enzyme has been extensively studied in animals (Dringen and Gutterer 2002;Erat et al 2003Erat et al , 2005Garcia-Alfonso et al 1993;Ulusu et al 2005), yeast (Colman and Black 1965;Huber and Brandt 1980;Massey and Williams 1965;Rakauskiene et al 1989), land plants (Anderson et al 1990;Connell and Mullet 1986;Madamanchi et al 1992) and cyanobacteria (Serrano et al 1984); but scarcely studied in diatoms or other algae (in Euglena gracilis strain Z, GRase has been previously studied by Montrichard et al 1999 andShigeoka et al 1987).…”
Section: Discussionsupporting
confidence: 87%
“…This activity value is very close to others reported for GRases purified from different sources Mannervik 1975, 1985;Chung and Hurlbert 1975;Dringen and Gutterer 2002;Serrano et al 1984). The enzyme has been extensively studied in animals (Dringen and Gutterer 2002;Erat et al 2003Erat et al , 2005Garcia-Alfonso et al 1993;Ulusu et al 2005), yeast (Colman and Black 1965;Huber and Brandt 1980;Massey and Williams 1965;Rakauskiene et al 1989), land plants (Anderson et al 1990;Connell and Mullet 1986;Madamanchi et al 1992) and cyanobacteria (Serrano et al 1984); but scarcely studied in diatoms or other algae (in Euglena gracilis strain Z, GRase has been previously studied by Montrichard et al 1999 andShigeoka et al 1987).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the optimum pH of the GR purified from the seed of the soybean plant was determined as pH 8.5 (Bilir, 2017). Moreover, it has been observed that GR optimum pH values purified from different organisms such as fish, sheep, chicken, humans and turtles are in similar ranges such as 6.5 -8.5 (Acan and Tezcan, 1989;Erat et al, 2005;Ogus and Ozer, 1998;Tekman et al, 2008;Willmore and Storey, 2007). The optimum concentration of substrate for the GR enzyme activity obtained from the leaf of A. maculatum was determined by the activity measurements using the optimum buffer solution at the optimum pH value containing different concentrations of NADPH (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The GR was collected after eluting by elution buffer 1 (E1) or elution buffer 2 (E2). (37) reported that chicken liver GR experienced maximum activity at 50 °C. These differences may reflect interspecific variation or a different adaptive mechanism for GR from the C. dromedarius liver.…”
Section: Discussionmentioning
confidence: 99%